On the cavitation-like pore blocking in ink-bottle pore: Evolution of hysteresis loop with neck size - Nguyen, P.; Fan, Chunyan; Do, D.; Nicholson, D. (American Chemical Society, 2013)
Studies of adsorption and desorption of argon at 87 K in model ink-bottle pores have been carried out using Monte Carlo simulation. We show that the isotherms can be constructed as a composite of isotherms for a set of unit cells with constant pore size. The mechanisms of adsorption and desorption in an ink-bottle pore can be easily understood from the characteristics of these unit cells, providing insight into how the hysteresis loop would evolve in shape and area when the neck size is varied. The key factor controlling the characteristics of the loop is the relative position of the condensation and evaporation pressures of these unit cells. Two features of particular interest are noted: (i) a pore blocking mechanism might be mistaken as a cavitation if cavitation is interpreted as a sudden change in the amount adsorbed along the desorption branch and (ii) the shape of the hysteresis loop switches from type H1 for small neck sizes to type H2 for larger necks but reverts back to type H1 when the neck size approaches the cavity size. © 2013 American Chemical Society.